Effectiveness Analysis Of The Mutual Agreement Procedure (MAP) As A Dispute Resolution Mechanism And The Advance Pricing Agreement (APA) As A Preventive Strategy For Transfer Pricing In Indonesia - Firgia Ekklesia Heilbron (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effectiveness of the Mutual Agreement Procedure (MAP) as a dispute resolution mechanism and the Advance Pricing Agreement (APA) as a preventive strategy for transfer pricing in Indonesia. This study employs a qualitative descriptive approach using secondary data in the form of tax regulations, OECD reports, and relevant academic literature. The findings indicate that, from a regulatory perspective, the implementation of MAP and APA in Indonesia is aligned with international standards, particularly following the issuance of PMK 172/PMK.03/2023. MAP has proven effective in reducing the risk of double taxation and providing a non-litigation alternative for dispute resolution, although it continues to face constraints such as lengthy processing times, the complexity of bilateral negotiations, and limited institutional capacity. Meanwhile, APA offers an advantage as a preventive instrument by providing legal certainty before transactions are carried out; however, its utilization remains relatively low due to administrative burdens, lengthy negotiation periods, and concerns regarding data confidentiality. Accordingly, the effectiveness of both mechanisms is strongly influenced by the quality of transfer pricing documentation, the preparedness of the tax authorities, and the level of taxpayer compliance. This study recommends strengthening institutional capacity, accelerating administrative procedures, and enhancing transparency to optimize the role of MAP and APA in supporting legal certainty and reducing international tax disputes in Indonesia.